(untitled) (Colombia Medica, 2016)
In 2015, the journal Science chose CRISPR-Cas9 technology as the most important technological advance of science in the last years. This magazine announced the beginning of a new era of biotechnology in which it would be possible to edit, correct and modify the genetic information of any cell in a feasible, fast and cheap way; and most importantly, with high precision. Its implementation in research laboratories in basic and applied sciences could help to develop therapeutic strategies for the health area with the main objective of healing diseases with a known genetic origin, and that until now have been impossible to cure